MODEL OF ORGANIZATION OF THE UNIVERSITY ECOSYSTEM FOR THE DEVELOPMENT OF STEM-EDUCATION - Kushnir, N.; Valko, N.; Osipova, N.; Bazanova, T. (Journal of Information Technologies in Education (ITE), 2018)
The development of artificial intelligence systems in the near future will lead to a reduction in routine, template work. The toolkit changes in most professions. There is a need for a quick retraining of a specialist and the use of computer systems. Nowadays, separate devices and systems have been created that can solve some of the problems that appear in everyday life. Therefore, STEM education is one of the directions that is in demand in society. During last few years in Ukraine there has been a rapid increase in the number of technical groups – robotics and programming. All of them are different of organization, types of classes, target audience. We made an effort to summarize the information received on this issue. In this article we analyze the situation on the market of educational services of the STEM-direction in Ukraine and in other countries, consider the existing technical and methodological support of STEM-education, as well as the experience of creating a STEM-school based on the post-graduate education center of Kherson State University. We describe the steps needed to create such a structure, its place in the educational system. Also we describe the experience of developing the material for the development of curricula, a series of events that promote the attraction of researches, and the introduction of digital technologies in the educational process. The pace and breadth of the STEM movement, as well as the support and interest of the state in Ukraine, show that, within three to five years, STEM-based methods and tools will be almost fully integrated into school curricula. At the same time, the material and technical support, as well as the professional development of teachers, are crucial for the pace of integration. The creation of a STEM center at the university, in which both future engineers and future teachers are trained, makes it possible to create a harmonious ecosystem in the region for the development of new technologies in the region.